DOES THE “COMMUNAL OWNERSHIP” OF WIFE EXIST IN THE 21ST CENTURY AFRICA? - Chidubem Nwaogaidu, John (International Journal of Psychosocial Rehabilitation, 2019)
The peculiar nature of African traditional marriage ritual, which is fundamentally communalistic, has remained in conflicting terms to the understanding of the Christian marriage. While Christianity emphasizes the individualistic content of marriage, the Igbo customary system recognizes the ‘communal ownership’ of wife. The kinship structure as drawn from the ‘alliance theory’ and the manner it endures through the marriage ritual in Igboland gives meaning to communal ownership. The major interest of this study is to evaluate the impact of Christianity on the marriage ritual and the communal ownership of wife. The study is carried out through a fieldwork and ethnographical research. The implication of this study is to understand the increasing marriage ritual interaction between Christianity and African Traditional Religion